THE EFFECT OF COMPANY CHARACTERISTICS AND CORPORATE GOVERNANCE ON TIMELINESS CORPORATE INTERNET REPORTING ON BANKING IN INDONESIA - Hamsyi, Nur Fitriana; Andriani, Silvia (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2021)
This research has the purpose of examining the effect of firm size, profitability, leverage, liquidity, public ownership, and the audit committee on the timeliness of corporate internet reporting in Indonesian banks. Types of data and data sources are pooling data and secondary data obtained from the financial statements of banking companies listed on the Indonesia Stock Exchange in 2018 - 2019. The sample obtained from the purposive sampling technique is as many as 39 companies tested for two consecutive years to obtain 78 data to be processed. The data analysis used is logistic regression analysis with the EViews 9 analysis tool. The results show that only company size has a positive effect. Meanwhile profitability, leverage, liquidity, public ownership, and the audit committee do not influence on the timeliness of corporate internet reporting.